Effects of Repetitive Transcranial Magnetic Stimulation on Upper Limb Motor Function and Serum Lipid Metabolomics in Patients With Ischemic Stroke: A Randomized Controlled Study - Meng‐Meng Li; Fei‐Yang Jia; Peng‐Cheng Liu; Hong‐Ya Liu; Gui‐Juan Zhou; Xin‐Ke Peng; Jin‐Ling Wang; Shu‐Zhi Li; Jing Liu; Jun Zhou (Brain and Behavior)
ABSTRACT Introduction Repetitive transcranial magnetic stimulation (rTMS) can reduce upper extremity motor dysfunction in patients with stroke. However, the optimal parameters and mechanisms of rTMS in stroke treatment remain unclear. Therefore, this study aimed to investigate the protective effect and mechanism of rTMS at different frequencies on the motor function of the upper limbs in patients with cerebral infarction using lipid metabolomics methods. Methods A total of 102 participants were randomly assigned to receive sham rTMS, 1 Hz rTMS, and 10 Hz rTMS. All participants were assessed at baseline and 2 weeks later using the Fugl‐Meyer Assessment upper extremity (FMA‐UE), National Institutes of Health Stroke Scale (NIHSS), Barthel scales, and serum collection—lipid metabolomics analysis of serum samples by untargeted metabolomics. Results The improvement in FMA‐UE, NIHSS, and Barthel scores was more significant in 1 and 10 Hz rTMS groups than in the sham rTMS treatment group (p < 0.05). The improvement effect of FMA‐UE (p < 0.05) and Barthel (p < 0.05) was significantly more potent with 1 Hz rTMS than with 10 Hz rTMS. There was no significant difference in NHISS (p > 0.05). After rTMS treatment of patients with ischemic stroke, differential metabolites of serum lipids included diacylglycerol phosphoinositide, triacylglycerol, and dialkyl glycerol. Conclusion Both low‐ and high‐frequency rTMS can effectively improve upper limb motor function and self‐care ability in patients with ischemic stroke. However, the effect of low‐frequency rTMS on improving upper limb motor function was more significant. Lipid metabolomics analysis revealed that high‐ and low‐frequency rTMS increased diacylglycerol phosphoinositide and triacylglycerol levels and reduced dialkyl glycerol levels.